DIFFERENCES OF SALIVA LEPTIN LEVELS IN CHILDREN WITH CHRONIC KIDNEY DISEASE ON HEMODIALYSIS AND HEALTHY CHILDREN (STUDY IN CHILDREN WITH GINGIVITIS) - NURMAIDA, BERTHAULI ESTER; Sutadi, Heriandi; B Budiardjo, Sarworini; Laksmi Hidayati, Eka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Analyze the difference of salivary leptin in between healthy children with gingivitis and hemodialysis (HD) children with gingivitis. Methods: A total of 20 children, ages 11â€“16-year-old with gingivitis, were chosen as subjects; 10 were on HD and 10 were healthy children. The level of salivary leptin was measured using the enzyme-linked immunosorbent assay method. Results: The results showed a significant difference of salivary leptin levels between the children on HD (61,300 Â± 4151 pg/ml) and the healthy children (57,200 Â± 3173 pg/ml). Conclusions: There is a significant difference in the salivary leptin levels in children on HD with gingivitis and healthy children with gingivitis.